Professional Activities (1930–1981) of Latvian-Born Lithuanian Architect and Engineer Karolis Reisonas (1894–1981) in Kaunas, Panevėžys and Adelaide Cities - Saladžinskas, Sigitas Vladas; Vaisvalavičienė, Kristina (History of Engineering Sciences and Institutions of Higher Education, 2019)
The article introduces the professional activities of Latvian-born Lithuanian architect and engineer Karolis Reisonas (in Latvian: Karolis Reisons; 1894–1981) in the second half of his life – from 1930 in Kaunas, Panevėžys and Adelaide cities – and his role in the history of Lithuanian architecture. K. Reisonas was one of the most prominent creators of modern 20th-century interwar Lithuanian architecture and together with other famous Lithuanian architects formed a special style of Kaunas modern architecture in interwar period. K. Reisonas is the author or co-author of representative buildings in Šiauliai, Kaunas and other Lithuanian cities, as well as in Riga and Adelaide cities. Architect and engineer K. Reisonas worked as Šiauliai City Engineer and Head of Municipal Construction Department (1922–1930), Director of Šiauliai Vocational School (1926), Consultant of Lithuanian Chamber of Agriculture (1927–1928), Head of Construction Department of Kaunas Municipality (1930– 1938), PPanevėžys City Engineer (1940) and Burgomaster (1941–1944). From 1949, the Reisonas family lived in Adelaide city, Australia. To his projects three monuments of independence were built in Lithuania – Monument of Independence in Šiauliai city, Podium of the Freedom Monument of Kaunas city and Roman Catholic Christ’s Resurrection Church in Kaunas city. Fourteen of buildings in Lithuania (in Kaunas and Šiauliai cities) designed by him are included in the list of cultural values of Lithuania. Early K. Reisonas’ projects are characterized by historism, elements of eclecticism and «brick style», later projects are characterized by austere rationalism, functionalism, adaptation to urban construction and cultural and historical context.